Effect of mixed fermentations with Starmerella bacillaris and Saccharomyces cerevisiae on management of malolactic fermentation. (August 2020) - Russo, Pasquale; Englezos, Vasileios; Capozzi, Vittorio; Pollon, Matteo; Río Segade, Susana; Rantsiou, Kalliopi; Spano, Giuseppe; Cocolin, Luca
Graphical abstract: Highlights: Interactions among Starm. bacillaris and LAB were explored in wine mixed fermentations. MLF was differently affected depending on the strains and yeast inoculation protocol. Couple Starmerella /LAB stimulated, inhibited, or unaffected the outcome of the MLF in co-inoculum. O. oeni always performed MLF successfully and minimally impacting on the wine aromatic profile. Strain-depending interactions affected time of vinification and quality of the wine. Abstract: This work aims to improve the management of the malolactic fermentation (MLF) in red wines by elucidating the interactions between Starmerella bacillaris and Saccharomyces cerevisiae in mixed fermentations and malolactic bacteria. Two Starm. bacillaris strains were individually used in mixed fermentations with a commercial S. cerevisiae . MLF was performed using two autochthonous Lactobacillus plantarum and one commercial Oenococcus oeni inoculated following a simultaneous (together with S. cerevisiae ) or sequential (at the end of alcoholic fermentation) approach. The impact of yeast inoculation on the progress of MLF was investigated by monitoring the viable microbial populations and the evolution of the main oenological parameters, as well as the volatile organic composition of the wines obtained in mixed and pure micro-scale winemaking trials. Our results indicated that MLF was stimulated, inhibited, or unaffected in mixed fermentations depending on the strains and on the regime of inoculation. O. oeni was able to perform MLF under all experimental conditions, and it showed a minimal impact on the volatile organic compounds of the wine. L. plantarum was unable to perform MLF in sequential inoculation assays, and strain-depending interactions with Starm. bacillaris were indicated as factor affecting the outcome of MLF. Moreover, uncompleted MLF were related to a lower aromatic complexity of the wines. Our evidences indicate that tailored studies are needed to define the appropriate management of non- Saccharomyces and malolactic starter cultures in order to optimize some technological parameters (i.e. reduction of vinification time) and to improve qualitative features (i.e. primary and secondary metabolites production) of red wines.